Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/cche.10024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of xanthan and guar gums on starch digestibility and texture of rice flour blend bread

Abstract: Background and objectives The effects of adding xanthan and guar gums on starch digestibility and textural properties were examined in rice and wheat flour blend breads. Findings The addition of xanthan gum to the bread formula had a high impact on the staling of the crumb compared with guar gum. The addition of gums suppressed the recovery of the crumb after compression. The extent of starch digestion of the bread crumb was determined by an in vitro method using two types of bread crumb samples, milled sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
(37 reference statements)
4
11
0
Order By: Relevance
“…According to the results, at each time point from 0 to 14 d, it was observed that the gels incorporated with XT and GG as well as GCSPHs alone exhibited significantly lower values of the hardness than RS gel, indicating that XT, GG or GCSPHs can suppress the retrogradation of RS gel during storage. Our results are in good agreement with the previously reports, showing that the addition of XT, and GG can result in a reduced hardness of RS gels during storage which may be attributed to the difficulty rearrangement between amylose and amylopectin during crystallization due to the changed hydrogen bond in the presence of XT, and GG.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…According to the results, at each time point from 0 to 14 d, it was observed that the gels incorporated with XT and GG as well as GCSPHs alone exhibited significantly lower values of the hardness than RS gel, indicating that XT, GG or GCSPHs can suppress the retrogradation of RS gel during storage. Our results are in good agreement with the previously reports, showing that the addition of XT, and GG can result in a reduced hardness of RS gels during storage which may be attributed to the difficulty rearrangement between amylose and amylopectin during crystallization due to the changed hydrogen bond in the presence of XT, and GG.…”
Section: Resultssupporting
confidence: 93%
“…The presence of GCSPHs in GCSPHs‐XT gel produced a significant decrease due to the XT containing the charges and the strengthened interactions between the hydrophilic amino acid residuals of GCSPHs and water molecules in the RS gel. In addition to those aforementioned explains, the strengths of the intermolecular hydrogen bonds (between XT, amylose, and amylopectin) led to the reducing the firmness which is in agreement with the previous reports . Therefore, this study demonstrated that the GCSPHs exhibited a more pronounced effect on mitigating the retrogradation tendency of rice starch/ionic hydrocolloid (RS/XT) blends.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations